The making of a manager: Evidence from military officer training - Erik Grönqvist; Erik Lindqvist (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2015)
We show that officer training during the Swedish military service has a strong positive effect on the probability to attain a managerial position later in life. The most intense type of officer training increases the probability of becoming a civilian manager by about 5 percentage points, or 75 percent. Officer training also increases educational attainment post-military service. We argue that the effect on civilian leadership could be due to acquisition of leadership specific skills during the military service, and present suggestive evidence related to alternative mechanisms, such as signalling, networks, and training unrelated to leadership.
Keywords: J24; J31; I20; M51; 330; leadership; management; CEOs; non-cognitive skills; regression-discontinuity; program evaluation; conscription; military service; military officers; military leadership